Pengaruh Lama Usaha dan Pemahaman Akuntansi Terhadap Kualitas Laporan Keuangan UMKM: Studi Kasus Pada Umkm Di Kecamatan Jetis Bantul - Teguh Erawati; Lisna Setyaningrum (Jurnal Ilmiah Akuntansi Kesatuan, 2021)
Micro, Small and Medium Enterprises (MSMEs) face several obstacles so that in their business it is difficult to develop, one of which lies in financial management in their business activities so that in presenting financial reports, it creates a separate problem for MSMEs. The purpose of this study was to determine the effect of education level and educational background on the quality of MSME financial reports in Jetis District. The type of research used is quantitative with a descriptive approach. The population in this study were all MSMEs in Jetis District. The data collection method used a questionnaire with a total of 100 respondents. The results of this study provide an explanation that there is a significant positive effect on educational background on the quality of MSME financial reports. Whereas at the level of education is no significant effect on the quality of MSME financial reports.